Indicators of Diminished Organic Matter Degradation Potential of Polychaete Burrows in Philippine Mariculture Areas - Santander, Sheila Mae S.; San Diego-McGlone, Maria Lourdes; Reichardt, Wolfgang (2008)
Sediments from underneath fish cages and in mesocosm tanks were examined to establish indicators of diminished organic matter degradation potential of polychaete burrows from increased mariculture activities in Bolinao-Anda, Pangasinan, Philippines. Results showed that simple sediment characteristics may be used as sediment quality indicators to describe the contribution of burrows to biodegradable processes in sediments with extremely high deposition of organic particles. The indicators of diminished organic matter degradation potential of polychaete burrows are low redox potential (-113 to -150 mV for F. Spionidae and F. Eunicidae) at the 1 cm surface layer, absence or decreased size of burrow openings, presence of H2S, disappearance of apparent Redox Potential Discontinuity Layer (aRPD), formation of black sediment, and presence of Beggiatoa (sulfide oxidizing bacteria) and gas bubbles.
Keywords: Mariculture; Sediment analysis